PENERAPAN PENDEKATAN STUKTURAL THINK-PAIR-SHARE (TPS) UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA SISWA KELAS 7 PA SMPIT MASJID SYUHADA KOTABARU YOGYAKARTA - Suripah, Suripah (Universitas Ahmad Dahlan, 2012)
This research was to know the increase of result learn and interest of learning mathematics at SMP IT Masjid Syuhada Kotabaru Yogyakarta, in Oktober-November 2011. Subject were collected amount to 17 people. The data collecting instruments included an assay test and interest questionnaire. The data were analyzed using analysis descriptive. The result of research indicated the approach of Think-Pair-Share can improve result learn and interest of learning mathematics at chapter one variable linear equation. Where average interest of learning mathematics of the students was indicated high with average 41,18. The result of learning increased from 68,71 to 79,76.